Medical and Clinical Pathology Pre-Screening Visit and Enrolment Seasonal Variability in Healthy Volunteers - Yahya Murad,; Zaher A. Radi, (Journal of Basic & Applied Sciences, 2014)
In the pharmaceutical industry, selection of healthy volunteers is one of the foundations in phase I clinical trials and is a difficult and costly process. The objectives of this study were to evaluate the seasonal variability in recruiting healthy volunteers and examine the value of utilizing a pre-screen visit for healthy volunteers to generate a database pool that will be used in the routine screening process of phase I clinical research studies. We retrospectively studied a total of 1115 male and female volunteers who were scheduled for a medical and clinical pathology pre-screen visit over a one year period. Written consents were obtained from all individuals who participated in the study. Medical pre-screen visit included a full medical history and examination and electrocardiogram and clinical pathology (clinical chemistry, hematology and urinalysis). There was apparent seasonal variability in the participation of individuals in the pre-screen visit. Increased values of clinical chemistry values such as alanine aminotransferase and aspartate aminotransferase accounted for the majority of the clinically relevant increased values. Increased values of WBC’s and both platelets and mean corpuscular volume accounted for the lowest values. In urinalysis, the most prevalent abnormal values were increased WBC’s and red blood cells. No apparent differences were seen between sexes.Conducting medical and clinical pathology pre-screening visit is important as a source for healthy volunteer database pool to participate in phase I trials.